Letters of Dr. Syed Abdullah - Sikandar Hayat Mekan (بازیافت)
A letter claims a position of a significant document. This article introduces Dr. Abdullah's fourteen unpublished letters, for the first time ever. These letters addressed to re-knowned researcher and established critic of Iqbal, Prof. Dr. Rafi-ud-Din Hashmi. These letters are a discourse between two scholars that circumfuses academic and literary discussions. At the end, the article comprises of explanatory notes regarding those fourteen letters. It would make the  discernment and connotations of these letters easily  comprehendable. Previously, these letters were remotely away from the very sight of literary circles. These letters would hold the pedestal of an impactful, substantial and historic allusion after the publication of this article.